Биомедицинская электронная техника состояние и перспективы развития - Дацок, О. М. (ХНУРЭ, 2008)
A role and place of medical engineering in system of maintenance of protection of health of the man are considered. The status and prospects of manufacture of domestic medical engineering is analyzed. The modem status and prospects of development diagnostic and laboratory-analytical engineering is briefly analyzed.
Keywords: биомедицинская электронная техника; биомединженерия